100 Association of age-related left atrial remodeling with ischemic stroke in patients with normal sinus rhythm. (17th January 2020) - Bianco, F; De Caterina, R; Chandra, A; Goncalves, A; Aquila, I; Solomon, S D; Chen, L Y
Abstract: OnBehalf: The ARIC Study Background: Age-related left atrial (LA) structural/functional abnormalities in elderly patients with normal sinus rhythm and preserved ejection fraction may precede the development of overt atrial fibrillation, and also may be related to stroke. Purpose: To evaluate the association of 3-dimensional echocardiographic (3DE) atrial contractility parameters with subclinical cerebral infarcts (SCIs), as assessed by brain MRI, and clinically diagnosed stroke Methods: We studied 407 participants (mean age 76 ± 5 years, 40.5% male) from the Atherosclerosis Risk in Communities Neurocognitive Study (ARIC-NCS) without AF and who underwent a brain MRI and a 3DE examination in 2011-13. We defined 3 groups: those with no cerebral infarcts on brain MRI (NCIs, N = 315); those with MRI-diagnosed SCIs (N = 58); and those with clinically diagnosed stroke (N = 34). Results: While still within the normal range, LA indexed volume significantly increased across the 3 groups (P-trend = 0.01).This was accompanied by an increase in the LA global longitudinal strain (GLS), an echocardiographic index of LA reservoir function (P-trend = 0.004). E/e' divided by LA GLS—index of atrial stiffness—worsened across groups (P-trend = 0.005) and was independently associated with SCIs and Stroke, pooled together, [OR per 1 %-1, 1.97; 95% CI (1.24, 3.11), P = 0.004], and Stroke [OR per 1 %-1, 2.30; 95% CI (1.23, 4.30), P = 0.009]. LA GLS was marginally associated with an increased odd of SCIs [OR per 1 %, 1.07; 95% CI (1.01, 1.13), P = 0.014]. Conclusions: Among elderly participants with normal sinus rhythm and preserved ejection fraction in a large cohort study, markers of LA function and stiffness are associated with increased odds of subclinical infarcts and stroke. These data suggest that even subtle LA dysfunction, which may contribute to LA stasis, may predispose to subclinical cerebral infarcts and stroke.